Biphasic anaphylaxis after use of foam polidocanol sclerotherapy - Demir, Deniz; Kahraman, Nail; Şeker, İbrahim Burak; Gucu, Arif; Yavuz, Senol; Göncü, Mehmet Tuğrul (The European Research Journal, 2020)
Polidocanol is a sclerogenic agent commonly used for the treatment of varicose veins. Common complications such as hyperpigmentation, telangiectasia matting on skin may be observed in relation with foam sclerotherapy. Complications such as deep vein thrombosis, stroke and tissue necrosis are rarely seen. Fatal complications such as anaphylaxis are seen very uncommonly. A 50-year-old female patient underwent polidocanol foam sclerotherapy for left leg reticular varicosity (CEAP 2-3). Our patient has experienced biphasic anaphylaxis, which was observed as two attacks following the foam sclerotherapy. Biphasic anaphylaxis complication after the foam sclerotherapy is not known, this presentation may even be the first condition experienced ever.